"Suffocating" tumors by blocking adaptation to hypoxia: a new headway in melanoma immunotherapy. (1st January 2021) - Janji, Bassam; Chouaib, Salem
ABSTRACT: We recently reported that inhibiting Hypoxia-inducible Factor-1α ( Hif1a ) transcriptional activity improves melanoma immunotherapy by driving immune cells into the tumor microenvironment (TME). This Author's View provides additional perspectives on how hypoxia inhibitors combined with immunotherapy can be used as innovative approaches to improve the therapeutic benefit of melanoma patients.